2019
DOI: 10.1093/mnras/stz2048
|View full text |Cite
|
Sign up to set email alerts
|

Molecular envelope around the HII region RCW 120

Abstract: The H ii region RCW 120 is a well-known object, which is often considered as a target to verify theoretical models of gas and dust dynamics in the interstellar medium. However, the exact geometry of RCW 120 is still a matter of debate. In this work, we analyse observational data on molecular emission in RCW 120 and show that 13 CO(2-1) and C 18 O(2-1) lines are fitted by a 2D model representing a ring-like face-on structure. The changing of the C 18 O(3-2) line profile from double-peaked to single-peaked from … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 64 publications
(98 reference statements)
1
28
0
Order By: Relevance
“…The above arguments tend to favor an annular 3D morphology for RCW 120. This morphology is also favored by Kirsanova et al (2019) who modeled RCW 120 with a ringlike face-on structure to reproduce the observed 13 CO (2−1) and C 18 O (2−1) lines (see also Pavlyuchenkov et al 2013).…”
Section: D Morphology Of Rcw 120mentioning
confidence: 73%
See 1 more Smart Citation
“…The above arguments tend to favor an annular 3D morphology for RCW 120. This morphology is also favored by Kirsanova et al (2019) who modeled RCW 120 with a ringlike face-on structure to reproduce the observed 13 CO (2−1) and C 18 O (2−1) lines (see also Pavlyuchenkov et al 2013).…”
Section: D Morphology Of Rcw 120mentioning
confidence: 73%
“…The region is ionized by a single O6-8V/III star (Martins et al 2010). Due to its simple ovoid morphology and nearby location, 1.34 kpc (Deharveng et al 2009), it has been extensively studied in the recent past, especially in order to discuss the properties of star formation observed at its edges (Deharveng et al 2009;Zavagno et al 2010;Figueira et al 2017Figueira et al , 2018 and also to propose a scenario for its original formation by a cloud-cloud collision (Torii et al 2015) as well as its kinematics (Anderson et al 2015;Sánchez-Cruces et al 2018;Kohno et al 2018;Kirsanova et al 2019). The wealth of existing data on this region makes it ideal to study the impact of ionization on the structure of its dense PDR and its relation with the observed young star formation.…”
Section: Introductionmentioning
confidence: 99%
“…Several molecular transitions (MALT90 survey) such as tracers of hot core (CH 3 CN and HC 3 N) as well as a tracer of shock and outflow (SiO) are observed toward source 2, strongly indicating that an outflow is present. The profile is broad (Kirsanova et al 2019) and synonymous of the dynamics toward this core. SiO is also detected toward source 39, but as it is placed at the edge of the map, we did not extract the outflow because the edges are problematic due to the resampling process; however, it may contaminate the properties of the outflow at the location of source 2.…”
Section: Extraction Of the Wingsmentioning
confidence: 95%
“…RCW 120 is a well-studied Galactic H II region because of its ovoid shape and its relatively close distance (1.34 kpc, Russeil 2003;Zavagno et al 2007). Thanks to these advantages, this region has received a lot of attention from observers and simulations, and has been studied in several papers (Zavagno et al 2007(Zavagno et al , 2010(Zavagno et al , 2020Deharveng et al 2009;Anderson et al 2012Anderson et al , 2015Tremblin et al 2014;Kirsanova et al 2014Kirsanova et al , 2019Torii et al 2015;Walch et al 2015;Mackey et al 2016;Figueira et al 2017Figueira et al , 2018Marsh & Whitworth 2019). Figueira et al (2017) showed that two clumps observed at millimeter wavelength host different kinds of sources with respect to their evolutionary stage.…”
Section: Introductionmentioning
confidence: 99%
“…The distance between the peaks at the positions with the double-peaked line is approximately 1-1.5 km s −1 . Such a difference in velocities corresponds to the characteristic expansion rate of the sphericallysymmetric H regions (see, e.g., Kirsanova et al 2009Kirsanova et al , 2019. All this indicates the presence of several kinematic components along the line of sight near the ionizing stars.…”
Section: Resultsmentioning
confidence: 89%